2004
DOI: 10.1111/j.1365-313x.2004.02096.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive online detection of nitric oxide from plants and some other organisms by mass spectrometry

Abstract: SummaryAs nitric oxide (NO) is a key messenger in many organisms, reliable techniques for the detection of NO are essential. Here, it is shown that a combination of membrane inlet mass spectrometry (MIMS) and restriction capillary inlet mass spectrometry (RIMS) allows for the fast, speci®c, and non-invasive online detection of NO that has been emitted from tissue cultures of diverse organisms, or from whole plants. As an advantage over other NO assays, MIMS/RIMS discriminates nitrogen isotopes and simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 43 publications
3
54
0
3
Order By: Relevance
“…NO (approximately 1 nmol) and other gas detection from gaseous and liquid phases (Conrath et al, 2004). Another MS approach, where gaseous .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NO (approximately 1 nmol) and other gas detection from gaseous and liquid phases (Conrath et al, 2004). Another MS approach, where gaseous .…”
Section: Discussionmentioning
confidence: 99%
“…NO was passed through a polyethylene membrane into the vacuum of a mass spectrometer. A similar technique was employed by Conrath et al (2004) in the combined membrane inlet mass spectrometry (MIMS)/restriction capillary mass spectrometry (RIMS) approach, where . NO can either diffuse from a culture through a membrane (MIMS) or from the gas phase through a thin restriction capillary (RIMS) directly into a benchtop mass spectrometer (Conrath et al, 2004).…”
Section: Nitric Oxide (mentioning
confidence: 99%
See 1 more Smart Citation
“…Growth stimulation in plants with the strobilurin fungicides has been related to a reduction in the incidence of disease as well as increased nitrate uptake and assimilation in small grains (Köehle et al, 2003). Research has shown that pyraclostrobin was important in stimulating nitric oxide, a key messenger in plants (Conrath, Amoroso, Köhle, & Sultemeyer, 2004).…”
Section: Pyraclostrobin and Biomass Yieldmentioning
confidence: 99%
“…So, the application of pyraclostrobin affected net assimilasion rate. As reported by Conrath et al (2004), several researches shown that pyraclostrobin stimulated an increase in nitrate uptake and assimilation.…”
Section: Resultsmentioning
confidence: 84%